The agency of people living with HIV, living in impoverished areas of Chiapas in Mexico - Chong-Villarreal, Francisco (2017)
This paper aims to identify the dimensions of the agency (present past and future) in people with HIV(PV) in communities of Chiapas/México. The agency is the capacity to respond to the challenges that arise in life with resources that are available. Twenty interviews were conducted (12 men and 8 women) to people that live with the virus (PV) who had received the diagnosis at least one year earlier with an age range from 21 to 59 years. A script of open questions followed. Results: PV participate within the extended family to meet the needs of the disease.